Penerapan Deep Learnig dalam Pembelajaran Bahasa Indonesia di Kelas XI SMA Muhammadiyah Lamahala Jaya Kabupaten Flores timur - Sajidin Sajidin; Daroe Iswatiningsih (Istifkar: Media Transformasi Pendidikan, 2026)
This study examines the implementation of a deep learning approach in Indonesian Language instruction at grade XI of SMA Muhammadiyah Lamahala Jaya, East Flores Regency. A qualitative methodology with a case study design was employed, utilizing observation, interviews, and documentation as data collection techniques. Research subjects comprised the Indonesian Language teacher and eleventh-grade students. Findings reveal that the application of deep learning’s three core pillars, namely meaningful learning, mindful learning, and joyful learning, significantly enhanced students’ critical thinking skills and self-confidence. The mean post-test score reached 81.6, considerably higher than the 69.2 recorded by the conventional group. Nevertheless, implementation of this approach continues to face notable challenges, particularly inadequate technological infrastructure and insufficient teacher competence in integrating innovative instructional methods. The study recommends intensive professional development for educators and robust institutional policy support to optimize the application of deep learning in senior high schools, especially in remote areas.